1998
DOI: 10.1007/bf02577690
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparative pharmacological studies of a functional γ-aminobutyric acid (GABA) receptor cloned from the tobacco budworm,Heliothis virescens (Noctuidae:Lepidoptera)

Abstract: This paper reports the functional expression and pharmacological characterization of a full length complementary deoxyribonucleic acid (cDNA) (pIVY12) cloned from a Heliothis virescens fertilized egg cDNA library that encodes for a gamma-aminobutyric acid (GABA) receptor subunit (HVRDL-Ser 285). Two electrode voltage clamp recordings of Xenopus oocytes expressing the HVRDL GABA-gated chloride channel revealed robust chloride ion conductance in response to GABA and the GABAA receptor agonist, muscimol. Baclofen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 35 publications
5
21
1
Order By: Relevance
“…Similar levels of inhibition by 10 Ϫ5 moll Ϫ1 dieldrin in response to GABA-evoked currents after expression in Xenopus oocyte of the Drosophila and Heliothis RDL subunit were also reported by Wolff and Wingate (1998). Over the last 10 years three genes encoding subunits for GABA-mediated increases in Cl Ϫ conductance in Drosophila have been identified and cloned.…”
Section: Discussionsupporting
confidence: 63%
“…Similar levels of inhibition by 10 Ϫ5 moll Ϫ1 dieldrin in response to GABA-evoked currents after expression in Xenopus oocyte of the Drosophila and Heliothis RDL subunit were also reported by Wolff and Wingate (1998). Over the last 10 years three genes encoding subunits for GABA-mediated increases in Cl Ϫ conductance in Drosophila have been identified and cloned.…”
Section: Discussionsupporting
confidence: 63%
“…For example, bicuculline blocks ionotropic GABARs of some adult (Waldrop et al, 1987) and larval Manduca sexta abdominal ganglion neurons (Sattelle et al, 2003) as well as electrically evoked or odor-evoked inhibitory postsynaptic potentials and GABA responses in projection neurons of antennal lobes of this species (Christensen et al, 1998a,b). It is clear, however, that RDL and its equivalent cloned from Heliothis virescens (Wolff and Wingate, 1998) resemble, in their insensitivity to bicuculline, the majority of insect ionotropic GABARs.…”
Section: Rdl As a Model Of Native Insect Gaba Receptorsmentioning
confidence: 99%
“…Although RDL mimics well the agonist, competitive antagonist, and convulsant sites of insect GABARs, differences have emerged among RDL and known native insect GABARs in their sensitivity to benzodiazepines. For example, whereas the agonist responses of certain bicuculline-insensitive insect GABARs are enhanced by micromolar concentrations of flunitrazepam (Sattelle et al, 1988), the GABA responses of RDL homomers (Millar et al, 1994) or its H. virescens equivalent (Wolff and Wingate, 1998) are unaffected by flunitrazepam (100 M). More importantly, insect native GABARs and RDL homomers are both enhanced by lower concentrations of 4Ј-chlorodiazepam (Ro5-4864) (it inhibits native receptors at higher concentrations; R. Higashino and D. B. Sattelle, unpublished obervations), although RDL receptors were approximately 100-fold less sensitive to this compound than native insect receptors (Sattelle et al, 1988;Buckingham et al, 1996;Hosie and Sattelle, 1996b).…”
Section: Rdl As a Model Of Native Insect Gaba Receptorsmentioning
confidence: 99%
“…On the other hand, Rdl is also a component of GluCls in insects (Ludmerer et al, 2002), and although this may be unimportant in terms of dieldrin resistance, it could play a role in the development of resistance of fipronil, which also potently blocks GluCls. Heterologously expressed Rdl homomultimers containing the resistance mutation may display reduced sensitivity to fipronil in some cases (Wolff and Wingate, 1998) that, although much less than the resistance to dieldrin, could lead to moderate levels of resistance to fipronil in some species, which is in fact seen (Cole et al, 1995). Studies of the action of fipronil against native GABA and nondesensitizing GluCls in insects with the Rdl resistance mechanism are needed to fully understand the moderate resistance to fipronil.…”
Section: Fipronil On Glutamate Chloride Channels 199mentioning
confidence: 99%
“…Furthermore, after several years of use in more than 60 countries, the field performance of fipronil has not been hampered by resistance. The Ala-Ser mutation of the Drosophila (DMRd1) GABA receptor is not associated with reduced fipronil sensitivity (Hosie et al, 1995), but equivalent mutation of Heliothis GABA receptor (HVDRL) showed reduced sensitivity to fipronil (Wolff and Wingate, 1998). Thus, a target site other than Rdl GABA receptor might be involved in the effectiveness of fipronil on dieldrin-resistant insects.…”
mentioning
confidence: 98%